Pengaruh Sistem Akuntansi Pemerintah Daerah dan Penganggaran Berbasis Kinerja Terhadap Akuntabilitas Kinerja Pemerintahan Daerah Kabupaten Bandung (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effect of the Regional Government Accounting System and Performance-Based Budgeting on the Performance Accountability of the Regional Government in Bandung Regency. Using a quantitative approach, the data were collected through questionnaires distributed to 88 respondents across 22 local government organizations (OPD). The data were analyzed using multiple linear regression to determine both partial and simultaneous influences. The findings show that both variables have a significant and positive effect on performance accountability, with the accounting system having a more dominant influence. This implies that improving financial reporting and aligning budgets with measurable performance can enhance transparency, efficiency, and accountability in public sector governance. The study provides theoretical insight and practical recommendations for strengthening public financial management systems.